2023
DOI: 10.1108/jsm-11-2022-0363
|View full text |Cite
|
Sign up to set email alerts
|

How do influencers’ characteristics affect followers’ stickiness and well-being in the social media context?

Abstract: Purpose Drawing on source credibility theory, this study aims to explore the relationship between influencers’ characteristics and followers’ well-being through followers’ stickiness to influencers’ channels or posts. Design/methodology/approach The authors gathered data through an online survey of 450 followers. The proposed hypotheses were examined using structural equation modeling. Findings Results reveal that trustworthiness and physical attractiveness positively affect followers’ stickiness to influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…An influencer who is considered trustworthy is more likely to have loyal followers who believe in his/her recommendations and opinions. Trustworthiness is crucial for building and maintaining a strong relationship with followers, which in turn influences their purchase decision and brand preferences [64,65].…”
Section: C) Trustworthinessmentioning
confidence: 99%
“…An influencer who is considered trustworthy is more likely to have loyal followers who believe in his/her recommendations and opinions. Trustworthiness is crucial for building and maintaining a strong relationship with followers, which in turn influences their purchase decision and brand preferences [64,65].…”
Section: C) Trustworthinessmentioning
confidence: 99%
“…Attention represents a consumer's attentiveness to the focal engagement object (So et al, 2014(So et al, , 2016a. Consumers' brand-related attention also fosters stickiness: social media research has shown that influencers' characteristics can elicit users' focus, leading them to return to the influencer and/or the brand (Lu & Chen, 2023).…”
Section: Customer Engagementmentioning
confidence: 99%
“…An influencer who is considered trustworthy is more likely to have loyal followers who believe in his/her recommendations and opinions. Trustworthiness is crucial for building and maintaining a strong relationship with followers, which, in turn, influences the followers' purchase decisions and brand preferences [65,66].…”
Section: (C) Trustworthinessmentioning
confidence: 99%